Knowledge sharing and Self Awareness for Environmental Cleanliness - Vera Firdaus; Wisnu P. Setiyono; Mas Oetardjo; Denisa F. Syahputri; Nur L. Maulidyah (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article presents a community service initiative aimed at enhancing the self-awareness of women (housewives) in Durung Banjar Village, Indonesia, regarding environmental cleanliness and waste management. Through counseling and knowledge sharing activities, the project fostered a deeper understanding of the impacts of cleanliness on the ecosystem. The methodology involved observation, permit management, activity design, and engaging sessions encompassing counseling, videos, and discussions. The study's outcomes underscored the significance of waste processing for economic benefits, contributing to a sustainable and environmentally conscious society. The documented results, including activity videos and news articles, highlight the importance of promoting environmental stewardship and sustainable practices among global communities. Highlights: Importance of Women's Empowerment: The community service initiative focused on empowering women to take a leading role in maintaining environmental cleanliness and waste management, fostering a positive impact on their households and surroundings. Knowledge Sharing for Environmental Awareness: Through counseling and various interactive activities, the project successfully shared valuable insights and information on the significance of environmental cleanliness, cultivating a deeper understanding among participants. Promoting Sustainable Practices: The study emphasized the crucial role of waste processing in generating economic opportunities, underlining the need for sustainable practices that benefit both the environment and the community. Keywords: Women, Environmental Cleanliness, Waste Management, Knowledge Sharing, Community Service